Training course in applied econometric analysis for young economists/researchers in Uzbekistan: December 2023 - CGIAR (CGIAR, 2023)
The stakeholder consultations organized by the CGIAR Initiative on Fragility to Resilience in Central and West Asia and North Africa (F2R-CWANA) in Uzbekistan1 demonstrated a significant need in Uzbekistan for training in quantitative policy analysis and research, including applied data analysis. In the past, IFPRI organized similar training courses in applied econometric analysis for economists and researchers from Central Asia in collaboration with the Westminster International University in Tashkent (WIUT) from 2014 to 2019. The courses received positive feedback from local stakeholders, including policymakers, universities, research institutes, and individual researchers. To meet the growing demand and interest in modern methods and tools of applied policy analysis and research in the country, IFPRI and ICARDA, in collaboration with the International Scientific Center for Agri-Food Development (ISCAD) under the Ministry of Agriculture and Rural Development and WIUT, organized two training courses in 2023. The first training course in applied quantitative methods and data analysis was held in Tashkent from January 16 through 20, 2023. This was a foundational course focused on data analysis, the statistical foundations of applied policy research, and an introduction to econometric analysis. The second training course on applied econometric analysis was organized from December 11 through 15, 2023. This course concentrated on more advanced methods of applied econometric analysis, particularly on model diagnostics and specification, causality, and identification issues. This course is summarized in the following sections of this report.